Improving Literacy Comprehension Skills in Children at The Pendua Daya Hamlet - Umah, Hafizatul; Sahid, Lintia Purnama; Pahira, Sukmawati; Armita, Rena; Hamdani, Muh. (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research aims to improve the comprehension skills of calistung (reading, writing, and counting) for children in the Pendua Daya Hamlet Hall. The background of this research is based on the low basic ability of children in understanding reading, writing letters correctly, and counting simply, which is caused by a lack of learning motivation and limited interesting learning methods. This research uses a descriptive qualitative approach with the subject of elementary school-age children who participate in learning activities in the hamlet hall. Data collection techniques are carried out through observation, interviews, and documentation during the learning process. The research results show that the use of interactive learning methods, such as educational games, visual media, and direct practice-based learning activities, can increase children's interest and understanding of calistung. Children become more active, enthusiastic, and show an increase in reading simple words, writing short sentences, and basic numeracy. The conclusion of this study is that the implementation of creative and fun learning methods can be an effective strategy in improving children's calistung comprehension skills in non-formal environments such as hamlets.